Effects of drought-tolerant rice varieties and alternate wetting and drying on irrigation water, rice yield, water productivity and farmers’ income - Akpoffo, Marius A.Y.; Kone, Pierre; Guindo, Jonathan; Dossou-Yovo, Elliott Ronald (2024)
"In the context of climate change and its corollaries of resources challenges, it urges to promote climate smart agriculture to sustainably produce sufficient food to meet the demands of the ever-growing global population with limited resources. Growing drought-tolerant rice variety using water-saving irrigation technologies may reduce water use and enhance productivity and food security. The objective of this study was to evaluate the effects of drought-tolerant rice varieties and alternate wetting and drying (AWD) on irrigation water, rice yield, water productivity and farmers’ income. A 2-years field experiment was conducted from 2023 to 2024 at Selingue and Mbewani in Mali. The experimental design was a split plot: water management (continuous flooding: CF; alternate wetting and drying: AWD; and farmers’ practices: FP) as the main factor and varieties (ARICA3, GAMBIACA, KAFACI 1 and Sutura) as sub-factor with 3 replicates. The results revealed significant effects of water management and variety on agronomic and economic parameters. Compared to FP and CF, AWD resulted in the highest labour productivity (99.9 kg.day-1) and water productivity (1 kg.m-3), nutrient use efficiencies (88 kg.kg-1; 564.2 kg.kg-1 and 564.2 kg.kg-1) and the highest grain yield recorded (9.6 t.ha-1). The net benefit achieved under AWD (1758.5 USD.ha-1) was almost double of the one recorded under CF (924.4 USD.ha-1). ARICA3, KAFACI 1 and Sutura had higher yields and net benefit ranged (1497.4 - 1716.3 USD.ha-1) compared to the local check Gambiaka (704.3 USD.ha-1). The interactions between water management and varieties were significant with the highest yield and net benefit recorded under AWD combined with Sutura. We therefore concluded that bundling AWD and Sutura could be recommended to the smallholder farmers to increase water and labour productivity, rice yield and farmers’ income in irrigated systems in Mali."